Pemulihan Usaha Kecil dan Menengah di Aceh - Musa Asy'ariy (Unisia, 2005)
To reconstruct the econoc life of Aceh after happening tsunami need economical development strategic with focusing on education to increase human resource quality. Besides, to conduct economical development based on justice and local wisdom of people culture. Based on just economical approach and develop productive business culture, it was expected that economical recovery can be conducted step by step. The aim of these programs is to rebuild self confident of Aceh people. For that reason, Indonesian government should role for people of Aceh to participate fairly